Retrograde approach for percutaneous closure in a patient with ruptured sinus of Valsalva - Erdogan İlkay; Özlem Özcan Celebi; Fehmi Kaçmaz; Kutluk Pampal (Türk Kardiyoloji Derneği Arşivi, 2014)
In this report, we present a 37-year-old male with ruptured right sinus of Valsalva. He was treated by percutaneous closure of the rupture using the retrograde approach. The procedure was performed successfully within 26 minutes. We think this approach may be used in future instead of the antegrade approach.